Monitoring the snow leopard population in the Altai Mountains (Chikhachev Ridge, Siberia) - Parkhomenko, Maksim R.; Antonenko, Tatyana V.; Matsyura, Alex V.; Spitsyn, Sergey V. (Zenodo, 2023)
The snow leopard population has been monitored on the Chikhacvhev Ridge for 10 years since 2011 using camera traps. In 2021, a male was recorded. We recorded several concurrent predatory species, like red fox, Pallas’s cat, wolverine, and brown bear, and prey species Altai marmots. The snow leopards performed visual and olfactory marking at their area. We concluded that snow leopards in this transboundary mountain area were active at temperatures up to 3 °C in summer period.